The Influence of Sharia Compliance and Sharia Corporate Governance on the Financial Performance of Sharia Commercial Banks - Diana Djuwita; Nur Eka Setiowati; Umi Kulsum (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2019)
Abstract                This study aims to examine the effect of Sharia Compliance and Islamic Corporate Governace on Financial Performance in Islamic Commercial Banks. The population in this study were all Sharia Commercial Banks (BUS) registered at Bank Indonesia in the period 2013 to 2017. The samples were selected using the purposive sampling method. The total sample used in this study amounted to 8 Islamic Commercial Banks with a 5-year research period. The analytical method used in this study is multiple regression that is processed using SPSS version 20. The results of this study indicate that the Sharia Compliance variable has a significant negative effect on Financial Performance in Islamic commercial banks and the Islamic Corporate Governance variable has a significant negative effect on Financial Performance at sharia commercial bank. While simultaneously, Sharia Compliance and Islamic Corporate Governance have a significant positive effect on Financial Performance at Islamic commercial banks.  Keywords: Sharia Compliance, Islamic Corporate Governance, Financial Performance and Sharia Commercial Bank  Abstrak Penelitian ini bertujuan untuk menguji pengaruh Sharia Compliance dan Islamic Corporate Governace terhadap Kinerja Keuangan pada Bank Umum Syariah. Populasi dalam penelitian ini adalah seluruh Bank Umum Syariah (BUS) yang terdaftar di Bank Indonesia pada periode 2013 sampai dengan 2017. Sampel dipilih dengan menggunakan metode purposive sampling. Total sampel yang digunakan dalam penelitian ini berjumlah 8 Bank Umum Syariah dengan periode penelitian 5 tahun. Metode analisis yang digunakan dalam penelitian ini adalah regresi berganda yang diolah menggunakan SPSS versi 20. Hasil dari penelitian ini menunjukkan bahwa variabel Sharia Compliance memiliki pengaruh negatif signifikan terhadap Kinerja Keuangan pada bank umum syariah dan variabel Islamic Corporate Governance memiliki pengaruh negatif signifikan terhadap Kinerja Keuangan pada bank umum syariah. Sedangkan secara simultan, Sharia Compliance dan Islamic Corporate Governance berpengaruh positif signifikan terhadap Kinerja Keuangan pada bank umum syariah.  Kata Kunci: Sharia Compliance, Islamic Corporate Governance, Kinerja Keuangan, dan Bank Umum Syariah